App-based intervention for cardiovascular and diabetes risk awareness and prevention. (11th May 2022) - Buss, V; Varnfield, M; Harris, M; Barr, M
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Centre for Primary Health Care and Equity, University of New South WalesAustralian e-Health Research Centre, Commonwealth Scientific and Industrial Research Organisation Background: Cardiovascular disease and type 2 diabetes mellitus are highly prevalent worldwide. They have similar risk factors, and people with diabetes have a two- to threefold increased risk of myocardial infarction and stroke. Many of the risk factors are lifestyle related. Hence, behaviour change interventions have the potential to decrease the risk for cardiovascular disease and type 2 diabetes mellitus. Purpose: We aimed to develop and evaluate an app-based intervention for the primary prevention of cardiovascular disease and type 2 diabetes mellitus. Methods: We developed our app using the methodology by Tombor and colleagues for the development of digital behaviour change interventions. We used the Behaviour Change Wheel and embedded 12 behaviour change techniques. The three core modules of the app consisted of i) risk scores for 5-year cardiovascular disease and type 2 diabetes mellitus; ii) goal setting and tracking functions for smoking, alcohol intake, diet, and physical activity; and iii) education about the diseases and risk factors. With the app prototype, we conducted usability testing via an iterative approach. We interviewed the participants and used their feedback to improve the app design. Next, we conducted a feasibility study with the new version to assess whether participants would use the app over three months. We were interested in drop-out from the intervention, adherence to app use, and usability of the app. We received ethics approval for both studies and written consent from all participants. Results: The usability testing consisted of two rounds. For each round, we had five participants who were on average 57 years old. In the first round, three participants experienced a technical error that stopped them from completing the registration. From those who were able to register, five rated the app as above average according to the System Usability Scale. Overall, the participants found the app easy to use and indicated that they were interested to use it frequently. We included some additional features based on the preferences of the participants in the usability testing. For the feasibility study, we recruited 47 participants aged 45 years and older who were free of cardiovascular disease and type 2 diabetes mellitus at baseline, with a balanced distribution of age (45-64 years and ≥65 years) and gender. From those participants, four withdrew from the study immediately after providing consent and the remainder continued using the app for varying periods of time. Conclusions: We ensured that the app is based on the theory of behaviour change and scientific evidence. We used a stepwise approach to improve the app design and to test the feasibility of the intervention. The next step will be to develop a framework for a larger trial that implements the intervention into the existing healthcare setting and investigates its effectiveness.